Copper modified carbon nitride as fluorescence sensor for nitrate ions - Jasman, Siti Maryam (INSTITUT KIMIA MALAYSIA, 2016)
Carbon nitride (CN) has attracted tremendous interest in numerous applications owing to its unique chemical properties. In this study, newly developed copper modified CN composites were prepared and tested as fluorescence sensor for the detection of nitrate ions (NO3-). The CN was prepared by using urea as a precursor by using thermal polymerization technique and calcined at 823 K for 4 hours. Modification of CN with copper species was carried out via impregnation of copper(II) acetylacetonate onto the CN, followed by thermal reduction process at 473 K for 2 hours. The structure and chemical properties of CN and copper modified CN composites were investigated via X-ray diffraction (XRD), Fourier transform infra-red (FTIR), diffuse reflectance ultraviolet-visible (DR UV-Vis) and fluorescence spectroscopies. Three excitation wavelengths represented as C=N, C=O and C-N moieties were suggested to contribute as sensing sites in CN and copper modified CN composites. The sensing capabilities of CN and copper modified CN composites toward NO3- in the range of 300 to 1800 µM were determined via a quenching technique. The quenching efficiencies (KSV) of CN and copper modified CN composites were obtained from the Stern-Volmer plot. Among three excitation peaks of CN, C=N sites were found to be the most sensitive site having the strongest interaction with NO3-. At the optimum loading of Cu (0.1 mol%), the KSV of CN was improved from 2.1 x 10-4 to 2.5 x 10-4 µM-1. This study showed that with the addition of copper as modifier, the performance of CN can be improved and the composite can be used as potential fluorescence sensor for the detection of NO3-.